2017
DOI: 10.1177/0040517517700194
|View full text |Cite
|
Sign up to set email alerts
|

Study on the effect of the sanitary properties of microfiber synthetic leather base by using a filling agent

Abstract: In the manufacturing process of the microfiber synthetic leather, various types of filling agents were selected to fill the microfiber synthetic leather base to improve the sanitary properties, in which a zirconium tanning agent was used commonly. In this study, the softness, moisture absorption, water vapor permeability and mechanical properties of the base were used as indexes, and the type and dosage of the filling agent were optimized. The results indicated that the sanitary properties of the base treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…The polyamide fiber is a kind of synthetic fiber with the molecular chain composed of the repeated amide group (CONH) as well as −COOH and −NH 2 at the end of the molecular chain . Compared with cotton, the polyamide fiber nonwoven material has poor moisture absorption performance and stuffiness. Collagen with many hydrophilic groups modified on polyamide fiber nonwoven materials can effectively improve moisture permeability. Based on the morphological characteristics of microspheres, the leather waste collagen in the form of microspheres was modified on the polyamide fiber nonwoven material, which can not only keep collagen off the original voids on the material but also greatly improve moisture permeability.…”
Section: Introductionmentioning
confidence: 99%
“…The polyamide fiber is a kind of synthetic fiber with the molecular chain composed of the repeated amide group (CONH) as well as −COOH and −NH 2 at the end of the molecular chain . Compared with cotton, the polyamide fiber nonwoven material has poor moisture absorption performance and stuffiness. Collagen with many hydrophilic groups modified on polyamide fiber nonwoven materials can effectively improve moisture permeability. Based on the morphological characteristics of microspheres, the leather waste collagen in the form of microspheres was modified on the polyamide fiber nonwoven material, which can not only keep collagen off the original voids on the material but also greatly improve moisture permeability.…”
Section: Introductionmentioning
confidence: 99%
“…A series of studies have been carried out to improve the moisture permeability of microfiber synthetic leather substrates, but the studies have focused mainly on modifying the surface of polyamide fibers by introducing a large number of hydrophilic groups to improve the moisture absorption and permeability of the substrates. However, a few studies have been reported on modifications or substitution studies around polyurethane fillers.…”
Section: Introductionmentioning
confidence: 99%
“…Pembuatan kulit sintetis dapat menggunakan bahan baku polimer beragam, antara lain PVC (Musthofa et al, 1997), PU, poliamida (Liu et al, 2015;Qiang et al, 2017;Roh et al, 2013), akrilik, atau polyester (Ho, 2015). Basis polimer perlu ditambahkan bahan pembantu seperti pemlastis, penstabil, bahan pengisi, pigmen serta bahan penguat untuk mendapatkan kulit sintetis dengan sifat fisis dan mekanis yang diinginkan.…”
unclassified